CryptoImperforate Hymen with a Huge Abdominal Mass and Massive Hematocolpometra in a 15-Year-Old Girlmenorrhea with a Huge Abdominal Mass and Massive Hematocolpometra in a 15-Year-Old Girl - Oluwadare Martins Ipinnimo; ifeanyi Martins Okoye; Kayode Adeniyi; Tope Michael Ipinnimo; Oluseyi Igbekele Ipinnimo; Chukwunonso Onyejide Ezrah (Babcock University Medical Journal, 2023)
Background: Imperforate hymen is one of the commonest embryological defects of the lower genital tract which occurs due to failure of canalization of the sinovaginal bulb. Its incidence is 1 in 2000 girls.